Alterations in Intrinsic and Synaptic Properties of Hippocampal CA1 VIP Interneurons During Aging - Francavilla, Ruggiero; Guet-McCreight, Alexandre; Amalyan, Sona; Hui, Chin Wai; Topolnik, Dimitry; Michaud, Félix; Marino, Beatrice; Tremblay, Marie-Ève; Skinner, Frances K.; Topolnik, Lisa (Frontiers in Cellular Neuroscience, 2020)
Learning and memory deficits are hallmarks of the aging brain, with cortical neuronal circuits representing the main target in cognitive deterioration. While GABAergic inhibitory and disinhibitory circuits are critical in supporting cognitive processes, their roles in age-related cognitive decline remain largely unknown. Here, we examined the morphological and physiological properties of the hippocampal CA1 vasoactive intestinal peptide/calretinin-expressing (VIP+/CR+) type 3 interneuron-specific (I-S3) cells across mouse lifespan. Our data showed that while the number and morphological features of I-S3 cells remained unchanged, their firing and synaptic properties were significantly altered in old animals. In particular, the action potential duration and the level of steady-state depolarization were significantly increased in old animals in parallel with a significant decrease in the maximal firing frequency. Reducing the fast-delayed rectifier potassium or transient sodium conductances in I-S3 cell computational models could reproduce the age-related changes in I-S3 cell firing properties. However, experimental data revealed no difference in the activation properties of the Kv3.1 and A-type potassium currents, indicating that transient sodium together with other ion conductances may be responsible for the observed phenomena. Furthermore, I-S3 cells in aged mice received a stronger inhibitory drive due to concomitant increase in the amplitude and frequency of spontaneous inhibitory currents. These age-associated changes in the I-S3 cell properties occurred in parallel with an increased inhibition of their target interneurons and were associated with spatial memory deficits and increased anxiety. Taken together, these data indicate that VIP+/CR+ interneurons responsible for local circuit disinhibition survive during aging but exhibit significantly altered physiological properties, which may result in the increased inhibition of hippocampal interneurons and distorted mnemonic functions.